Antituberculosis Drug-induced Hepatotoxicity in Pediatric Tuberculosis - Vycke Yunivita; Muhammad Iqbal; Adi Utomo Suardi (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Hepatotoxicity is the most serious side effect caused by using oral antituberculosis (OAT) drugs. This study was performed to determine the characteristics of patients who had antituberculosis drug-induced hepatotoxicity (ADIH) among pediatric inpatient with pulmonary tuberculosis.Methods: This was a cross-sectional study with a total sampling of medical records taken from January–December 2012, including pediatric pulmonary tuberculosis inpatients aged <14 years old at the Department of Child Health of Dr. Hasan Sadikin General Hospital Bandung. The inclusion criteria were children with pulmonary tuberculosis who received OAT drugs. Patients with liver disease were excluded. Data on alanine and aspartate aminotransferase were collected and an increased level of serum aminotransferase was designated as hepatotoxicity.Results: In total, 86 medical records were obtained of whom 24 had ADIH, predominantly occurred in girls (71%), aged 5–9 years old (42%) and in the intensive phase of therapy (58%). Elevated serum alanine aminotransferase (58%), aspartate aminotransferasen (92%), and bilirubin (0.8%) were found. Malnutrition (46%) was common. The difference indeviation of liver function was statistically significant (p<000) between subjects with and without ADIH.Conclusions: Hepatotoxicity is most prominent in patients with malnutrition, girls aged 5–9 years old and in the intensive phase of therapy. Children with malnutrition during antituberculosis therapy are suggested to have a periodic liver function test monitoring to prevent the development of ADIH.